Rational and Experiential Thinking Style: Adaptation of Epstein's Inventory - А Melsovna Kustubayeva; А A Tolegenova; А T Kamzanova (Peoples' Friendship University of Russia (RUDN University), 2012)
This article is devoted to the study of the rational-experiential thinking style by using Epstein's Rational-Experiential Inventory (REI). The reliability analysis with Cronbach' Alpha showed the validity of the Russian version. Rational parameters were significantly higher than experiential. However, the higher score of experiential parameters were revealed in the female group compared to the male group.